CORRELATION BETWEEN HOUSEWIVES PREPAREDNESS IN FACING FLOOD WITH COPING MECHANISM IN TAMPING HAMLET, GRESIK REGENCY, INDONESIA - Wijono, Steven; Sincihu, Yudhiakuari; Young, Andre; Djoka, Marlyn; Soegeng, Kevin K; Yusup, David R; Hartono, Felicia P; Faustina, Danica; Agusalim, Yonathan; Pangestu, Vennessa M (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2024)
BACKGROUND: Indonesia is the largest archipelagic country in the world across the equator, located between two continents, two oceans, and located between three plates of the earth. This condition causes the risk of natural disasters such as floods. Tamping is a hamlet that often experiences flooding in Gresik Regency caused by the overflow of the Lamong tributary. This causes disruption in various sectors, especially the economy in the village, causing stress. AIM: Researchers want to know whether there is a correlation between community preparedness and coping mechanisms in dealing with floods. METHODS: The research design used was observational analytic with a cross sectional research design. In this study, the sample size was 59 people who were housewives in Tamping hamlet. The research data was taken through a questionnaire. RESULTS: Based on the results of data analysis using Spearman's test regarding the preparedness of housewives with coping mechanisms, the value of r=0.502 and significance value of p=0.001. CONCLUSION: There is a relationship between the preparedness of housewives in dealing with floods and coping mechanisms in Tamping Hemlet.